Analysing small insect glands with UV‐LDI MS: high‐resolution spatial analysis reveals the chemical composition and use of the osmeterium secretion in Themira superba (Sepsidae: Diptera). (22nd May 2014) - Araujo, D. P.; Tuan, M. J. M.; Yew, J. Y.; Meier, R.
Abstract For many insect species, pheromones are important communication tools, but chemical analysis and experimental study can be technically challenging because they require the detection and handling of complex chemicals in small quantities. One drawback of traditional mass spectrometry methods such as gas chromatography mass spectrometry is that whole‐body extractions from one to several hundred individuals are required, with the consequence that intra‐ and interindividual differences cannot be detected. Here, we used the recently introduced UV‐LDI MS (ultraviolet laser desorption/ionization mass spectrometry) to profile the 'osmeterium' of the sepsid fly Themira superba that is located on the edge of the hind tibia of males. Based on analyses of individual legs, we established that the gland produced a secretion that consisted of oxygenated hydrocarbons and putative isoprenoids. The secretion was first detected 24 h after eclosion, and its transfer to the wings of females during mating was demonstrated using UV‐LDI MS. We then tested whether the secretion had an anti‐aphrodisiac function, but experimental transfer of the secretion to virgin females did not affect mating success or copulation duration. Throughout the study, UV‐LDI MS proved invaluable, because it allowed tracking the natural and experimental transfer of small quantities of pheromones to specific body parts of small flies.